Minimization of power losses by traction-transportation vehicles at motion over a bearing surface that undergoes deformation - Mozhaiv, Oleksandr; Kuchuk, Heorhii; Shvets, Dmytro; Tretiak, Viktor; Tretiak, Mykhailo; Ostropilets, Vasyl; Markov, Viacheslav; Mozhaiev, Mykhailo; Kolisnyk, Tetiana; Nechayusov, Artem (Eastern-European Journal of Enterprise Technologies, 2019)
The paper reports the construction of a method aimed at minimizing power losses by traction-transportation vehicles at motion over a bearing surface resulting in the formation of ruts. The purpose of this study is to improve a traction efficiency coefficient for the off-road traction-transportation vehicles by determining and minimizing power losses related to forming a rut over a bearing surface under the action of a vehicle’s running gear. Improving the traction-transportation vehicles efficiency coefficient, which is 55÷65 %, is a priority in the development of agricultural mechanization. Part of the losses that are associated with the structure of a vehicle is almost not controlled in the process of operation. However, those substantial losses in running systems that reach 20 % can be managed. Control over them implies adjusting the settings of running systems in the traction-transportation vehicles to the condition of a bearing surface. Specifically, in the course of the study we analyzed the magnitudes of power required to displace elements in the system «a vehicle’s frame ‒ suspension ‒ running system ‒ deformed bearing surface» based on determining the force and kinematic factors. Based on direct measurements, we determine power losses when running systems form a rut over a bearing surface and when the running system’s elements are displaced. It has been proposed to determine the power spent to form a rut by multiplying the share of gravity force related to the respective engine by the destruction rate of the bearing surface. Based on the derived results and an analysis of experimental data, we concluded that the proposed procedure for determining the power losses related to the formation of a rut by traction-transportation vehicles on a bearing surface makes it possible to substantiate the choice of parameters for running systems in order to improve the traction efficiency coefficient